2016
DOI: 10.1111/ajo.12506
|View full text |Cite
|
Sign up to set email alerts
|

How do women seeking abortion choose between surgical and medical abortion? Perspectives from abortion service providers

Abstract: Women benefit from an alternative to surgical abortion and are well-placed to choose between the two methods, however, challenges remain to ensure that all women are enabled to make an informed choice. KIs identify the need to: promote the availability of medical abortion; address misconceptions about this method; and increase general practitioner involvement in the provision of medical abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…We developed a semi-structured interview schedule to explore with experts a range of issues related to abortion provision [22, 35, 36]. For part of the interview, we explored perceptions of Section 8 of the Abortion Law Reform Act and how it was being implemented by health care providers in the Victoria at the time of the interview (2015).…”
Section: Methodsmentioning
confidence: 99%
“…We developed a semi-structured interview schedule to explore with experts a range of issues related to abortion provision [22, 35, 36]. For part of the interview, we explored perceptions of Section 8 of the Abortion Law Reform Act and how it was being implemented by health care providers in the Victoria at the time of the interview (2015).…”
Section: Methodsmentioning
confidence: 99%
“…The interview covered participants' experiences providing abortion services, their role in the 2008 law reform, their views of both the intent and outcomes of abortion law reform, and remaining challenges. They were also asked about their experience of medical abortion and their views on the role of general practitioners in provision 19 20. Interviews were conducted by DN, and lasted between 30 minutes and 2 hours; de-identified audio-recordings were transcribed verbatim.…”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization supports the provision of abortion services at primary care level; 35 however, evidence of support for a GP-led abortion service internationally is inconclusive. It has been argued that GPs are ideally placed to provide a community-led abortion service, particularly in rural and regional communities, a view supported by a qualitative study of 15 experts in abortion service provision conducted in Australia, 36 though a descriptive-interpretive qualitative study of 32 Australian GPs found that some saw abortion as beyond the scope of their practice. 37 Some GPs had religious or moral objections; others regarded abortion provision as complicated and difficult, and while some GPs expressed interest in abortion provision, they were concerned about stigma and the impact it may have on perceptions of their practice and the views of colleagues.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%